Amylin‐mediated regulation of LRP1 by miR‐103/107 impairs β‐amyloid efflux. (1st February 2022) - Viswanathan, Velmurugan Gopal; Ly, Han; Sharma, Savita; Verma, Nirmal; Despa, Sanda; Nelson, Peter T; Goldstein, Larry B; Despa, Florin
Abstract: Background: To determine whether systemic pancreatic amylin dyshomeostasis impairs the efflux of amyloid‐β (Aβ) across the blood‐brain barrier (BBB), we studied cerebral microvessels in humans and a rat model of pancreatic amylin dyshomeostasis, and evaluated the effect of human amylin in an in vitro BBB model. Method: Brain sections from Alzheimer's Disease (AD) and cognitively unimpaired individuals were co‐stained with anti‐Aβ and anti‐amylin antibodies. In vivo analyses of Aβ efflux across the BBB were carried out in aged rats that express amyloid‐forming human amylin in pancreatic β‐cells and littermates expressing non‐amyloidogenic rat amylin. We also used an in vitro BBB model of Aβ transcytosis in which the endothelial cell monolayer was exposed to amylin‐mediated stress to determine whether amylin stress downregulates LRP1, the Aβ efflux transporter. This allowed us to use pharmacology to rescue the endothelial LRP1 Result: In human AD brains, Aβ accumulation within the perivascular space frequently co‐localizes with deposits of amylin in the vessel wall. In rats with pancreatic expression of amyloid‐forming human amylin, the high blood levels of human amylin promote amylin deposition in brain capillaries, increase brain Aβ level, lower plasma‐to‐brain Aβ ratio and suppress expression of LRP1 protein. In vitro BBB model experiment revealed that amylin‐induced stress downregulates LRP1 in endothelial cells through a miRNA‐based translational repression mechanism. Conclusion: High blood human amylin levels cause cerebral microvascular dysfunction and interferes with Aβ efflux across the BBB through miRNA‐mediated LRP1 downregulation. Lowering blood amylin level in early AD could improve Aβ clearance from the brain.